ACVIM consensus statement on the diagnosis of immune‐mediated hemolytic anemia in dogs and cats. (26th February 2019) - Garden, Oliver A.; Kidd, Linda; Mexas, Angela M.; Chang, Yu‐Mei; Jeffery, Unity; Blois, Shauna L.; Fogle, Jonathan E.; MacNeill, Amy L.; Lubas, George; Birkenheuer, Adam; Buoncompagni, Simona; Dandrieux, Julien R. S.; et al.
Abstract : Immune‐mediated hemolytic anemia (IMHA) is an important cause of morbidity and mortality in dogs. IMHA also occurs in cats, although less commonly. IMHA is considered secondary when it can be attributed to an underlying disease, and as primary (idiopathic) if no cause is found. Eliminating diseases that cause IMHA may attenuate or stop immune‐mediated erythrocyte destruction, and adverse consequences of long‐term immunosuppressive treatment can be avoided. Infections, cancer, drugs, vaccines, and inflammatory processes may be underlying causes of IMHA. Evidence for these comorbidities has not been systematically evaluated, rendering evidence‐based decisions difficult. We identified and extracted data from studies published in the veterinary literature and developed a novel tool for evaluation of evidence quality, using it to assess study design, diagnostic criteria for IMHA, comorbidities, and causality. Succinct evidence summary statements were written, along with screening recommendations. Statements were refined by conducting 3 iterations of Delphi review with panel and task force members. Commentary was solicited from several professional bodies to maximize clinical applicability before the recommendations were submitted. The resulting document is intended to provide clinical guidelines for diagnosis of, and underlying disease screening for, IMHA in dogs and cats. These should be implemented with consideration of animal, owner, and geographical factors.